MALI Scaling week workshop report - Ewell, Hanna Louise Deborah; Marius, Assogba Guy; Ouedraogo, Mathieu; Dossou Yovo, Elliott Ronald; Toure, Haissa; Diabate, Fatoumata; Bengaly, Oumar; Coulibaly, Issouf; Sangare, Modibo (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The AICCRA Mali Scaling Week workshop, held from May 5–7, 2025, in Bamako, brought together 38 participants from research, government, and development sectors to explore strategies for responsibly scaling Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) innovations. Through participatory sessions, the workshop deepened participants' understanding of the AICCRA Scaling Framework, encouraged reflection on barriers and enablers of scaling, and promoted systems thinking. The event focused on developing actionable roadmaps for four priority innovation bundles: Climate-Smart Rice Intensification, Integrated Resilient Rice-Fish Systems, Smart-Valley Development, and Inclusive Climate-Smart Rice Processing. Key outcomes included the identification of social and environmental risks, the articulation of responsible scaling pathways, and strengthened collaboration among actors. The workshop reinforced the importance of inclusive, context-specific solutions to achieve sustainable climate resilience and improved livelihoods in Mali.